Uncommon Pathogens Causing an Infrequent Disease - Two cases of Nonpuerperal Mastitis - Maio, Inês (2018)
Mastitis is an uncommon condition in children and nonpuerperal adolescents that is mostly caused by Staphylococcus aureus. We describe two cases, at different ages, without recalled trauma, and with an identification of atypical causative agents. Both patients were successfully treated with oral antibiotics.